HEALTH EDUCATION ON THE ROLE OF SPIRITUAL APPROACHES IN IMPROVING MOTIVATION OF HIV-INFECTED WOMEN AT THE TULUNGAGUNG AIDS COMMISSION - Mukarromah, Nur; Asri, Asri; Winata, Septian Galuh; Rofiqi, Erfan; Priyantini, Diah; Prabawati, Chlara Yunita (Universitas Airlangga, 2025)
The trend of HIV and AIDS cases in Indonesia still shows a high number and since 2002 there has been a phenomenon of many housewives with HIV positive. The high number of HIV and AIDS cases in women in Indonesia is a highlight that needs to be given a solution, because mothers who bear and care for children until adulthood, so it is very important to have high knowledge to prevent HIV and AIDS. Providing education also requires a spiritual approach to increase the motivation of mothers in preventing the emergence of new cases of HIV. The purpose of this community service is to provide health education to housewives to increase motivation in preventing transmission. Community service activities are carried out using direct methods by giving lectures and motivators to PLHIV in Tulungagung Regency. Activities are carried out in the meeting room, Tulungagung AIDS Control Commission. The method of implementing community service is counseling via powerpoint and video. Participants are 25 active female PLHIV who are members of the Tulungagung KPA. The results of the pre- and post-test assessments showed a significant difference and showed an increase from the results before counseling and after being given materials on spirituality, so that the motivation of female PLHIV increased. The results of the pre-test assessment showed that the average knowledge of housewives was 32.46%, while after being given health education the results increased to an average of 92.57%. Spirituality is an aspect of the human personality that empowers and influences individuals in living their lives. Spirituality is a dimension related to finding meaning and purpose in life, realizing the ability to use resources and strengths within oneself, having feelings related to God, oneself and the environment.